Writing for the ear, preaching from the heart - Giver-Johnston, Donna (Working preacher books, 2021)
In Writing for the Ear, Preaching from the Heart, Donna Giver-Johnston teaches preachers how to communicate effectively--how to get away from their notes and make a more personal connection with their listeners. Grounded in a theology of the incarnation, she offers a step-by-step method for writing sermons with the fewest, most impactful and memorable words and delivered by heart to communicate a message that captures the ears and hearts of listeners.